Incarcerated Thoracic Gastric Herniation after Nephrectomy: A Report of Two Cases. (16th May 2013) - Fitzgerald, Conall; Mc Cormack, Orla; Awan, Faisal; Elliott, Jessie; Ravi, Narayanasamy; Reynolds, John V.
Abstract : Iatrogenic diaphragmatic hernias can occur after abdominal or thoracic surgery. Acute presentation of a diaphragmatic hernia varies depending on the extent and nature of the organ which has herniated. The initial diagnosis can be challenging due to the nonspecific nature of the presenting symptoms. Delay in diagnosis poses a significant risk to the patient, and a rapid deterioration can occur in the context of strangulation. We outline two cases of acute gastric herniation through a defect in the diaphragm after an open and a laparoscopic nephrectomy. Both had characteristic findings on imaging, required emergency, surgery and had a successful outcome. Both cases highlight the potential for late presentation with non-specific symptoms and the necessity for urgent surgical management where gastric perfusion is compromised.